2019
DOI: 10.21809/rilemtechlett.2019.90
|View full text |Cite
|
Sign up to set email alerts
|

Recommended practice for reporting experimental data produced from studies on corrosion of steel in cementitious systems

Abstract: Experience has shown that many aspects of experimental design for studying steel corrosion in cementitious systems may significantly influence the obtained results. In the absence of standardized methods to study steel corrosion in concrete, researchers usually define their own test setups, which partially explains the large scatter and uncertainty in the aggregated published data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…It should be noted that with a defined target crack width, loading condition type and mix proportion, only one beam was studied although there were three rebars were involved in one beam. Replicated specimens under the same condition need to be further studied to verify the tendencies found in this study, as suggested in [33] for the recommended practice when reporting corrosion experimental data.…”
Section: Influence Of Fibresmentioning
confidence: 94%
“…It should be noted that with a defined target crack width, loading condition type and mix proportion, only one beam was studied although there were three rebars were involved in one beam. Replicated specimens under the same condition need to be further studied to verify the tendencies found in this study, as suggested in [33] for the recommended practice when reporting corrosion experimental data.…”
Section: Influence Of Fibresmentioning
confidence: 94%
“…Providing a description of the electrode configuration is important as all three electrodes can influence the measurement [360,361]. Hence, data on the type and position of the RE, the material and the geometry of the CE, and the use of surface electrodes with a specific electrolytic contact or embedded electrodes should be provided in all studies [362]. The linear polarization resistance (LPR) technique consists of applying a small potential sweep on the rebar around its open circuit potential (generally OCP±10-20 mV, either in the anodic or in the cathodic direction) and recording the resulting current (Fig.…”
Section: Measurement In Three-electrode Configurationmentioning
confidence: 99%
“…Specifically, there exists large scatter in the summarized critical Cl − contents of steel corrosion in cement-based materials due to the differences in experimental design such as composition of mixture, steel condition, inhomogeneity of mortar or concrete samples and corrosion detection methods. A recent research released by Isgor et al [67] highlighted the importance of the standardized method to investigate steel corrosion in cement-based materials. The multi-element sensor provides the possibility of monitoring corrosion parameters of steel and Cl f content in concrete pore solution by which critical Cl f content related to the occurrence of steel corrosion in concrete could be directly determined.…”
Section: Discussionmentioning
confidence: 99%